Implantation of endovascular stents for the obstructive right ventricular outflow tract - Sugiyama, H (Copyright 2005 by Heart, 2005)
Objectives: To evaluate the effectiveness and long term outcomes of catheter intervention for obstructive conduits between the right ventricle and pulmonary arteries. Design: Retrospective chart review. Setting: Tertiary care paediatric cardiology unit. Patients and interventions: 70 procedures in 68 children (median age at intervention 6 years, median interval after conduit insertion 3.4 years) were analysed. All children had haemodynamic indications for conduit replacement. Twenty four children underwent a second intervention (stent dilatation in 17, second stent implantation in seven). Results: Mean (SD) conduit pressure gradient decreased from 44 (18) mm Hg to 18 (12) mm Hg at the initial intervention (n  =  62, p < 0.001) and from 39 (15) mm Hg to 23 (10) mm Hg at the second intervention (n  =  16, p < 0.001). The percentage of the predicted right ventricular outflow area increased from 17 (9)% to 44 (22)% at the initial intervention (n  =  62, p < 0.001) and from 24 (8)% to 29 (11)% at the second intervention (n  =  21, p < 0.001). The conduit was subsequently replaced in 33 children. Freedom from conduit replacement from the time of stent implantation was 83%, 75%, and 47% at one, two, and five years, respectively, and from the time of the initial conduit surgery it was 87%, 64%, and 42% at five, eight, and 10 years, respectively. Body growth was maintained, no deaths were reported during follow up, and pulmonary insufficiency was well tolerated. Conclusion: A catheter treatment strategy for obstructive conduits is safe and effective in prolonging conduit function.